2016
DOI: 10.1021/acsbiomaterials.5b00511
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable Radiofrequency Responsive Nanoparticles for Augmented Thermal Ablation Combined with Triggered Drug Release in Liver Tumors

Abstract: Radiofrequency ablation (RFA) and doxorubicin (Dox) chemotherapy are separately approved for liver cancer therapy; however, both have limited success in the clinic due to suboptimal/nonuniform heating and systemic side effects, respectively. Here, we report a biodegradable nanoparticle (NP) system showing excellent RF hyperthermic response together with the ability to locally deliver Dox in the liver under RF trigger and control. The nanosystem was prepared by doping a clinically permissible dose (∼4.3 wt %, 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Our previous works on LSMO demonstrated that surface-grafted (colloidally stable) particles are capable of generating efficient thermal dose within a precisely controlled time duration. , This strategy was further exploited to develop stable, dispersible, cyto-hemocompatible PM@SPMNPs (i.e., PEG capped La 0.7 Sr 0.3 MnO 3 MNPs) with 6-fold improved SAR compared to their pristine counterpart. The enhancement of SAR and stimulated drug delivery resulted in an efficient internalization of drug by efficient thermal dose and the consequent increased cancer cell deaths. , Nevertheless, the results presented herein show that multimodality, i.e., DOX delivery (chemotherapy) with MFH (magneto-thermotherapy) using PM@SPMNPs is more effective than using single modality …”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Our previous works on LSMO demonstrated that surface-grafted (colloidally stable) particles are capable of generating efficient thermal dose within a precisely controlled time duration. , This strategy was further exploited to develop stable, dispersible, cyto-hemocompatible PM@SPMNPs (i.e., PEG capped La 0.7 Sr 0.3 MnO 3 MNPs) with 6-fold improved SAR compared to their pristine counterpart. The enhancement of SAR and stimulated drug delivery resulted in an efficient internalization of drug by efficient thermal dose and the consequent increased cancer cell deaths. , Nevertheless, the results presented herein show that multimodality, i.e., DOX delivery (chemotherapy) with MFH (magneto-thermotherapy) using PM@SPMNPs is more effective than using single modality …”
Section: Discussionmentioning
confidence: 76%
“…The enhancement of SAR and stimulated drug delivery resulted in an efficient internalization of drug by efficient thermal dose and the consequent increased cancer cell deaths. 37,38 Nevertheless, the results presented herein show that multimodality, i.e., DOX delivery (chemotherapy) with MFH (magneto-thermotherapy) using PM@SPMNPs is more effective than using single modality. 26 As it is known that certain NPs are highly effective but also toxic to patients, we performed a preliminary histopathological examination of exposed mice organs focusing on tissue damage, inflammation or lesions (Figure 6).…”
Section: Discussionmentioning
confidence: 78%
“…An additional study showed that biodegradable alginate nanoparticles combining radiofrequency triggered hyperthermia and triggered doxorubicin release could be used as an effective combination treatment method. In orthotopic rat liver tumor models, there was enhanced thermal ablation, controlled doxorubicin release, and imaging potential using MRI 150 . X-ray induced ionizing radiation and radiofrequency triggered hyperthermia are only a couple examples of some additional remotely triggered treatments that could be used in theranostic platforms.…”
Section: Additional Remotely Triggered Treatmentsmentioning
confidence: 99%
“…In recent years, integrated medical material for both diagnosis and simultaneous treatment has also become very attractive for doctors and patients because it can save a great deal of time and money. Based on this requirement, MNPs, previously used as a powerful diagnostic tool, are being considered as theranostic delivery systems combining imaging agents and effective therapeutic drugs [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%